HUBUNGAN KEHARMONISAN KELUARGA DENGAN KETERAMPILAN SOSIAL PESERTA DIDIK DI KELAS X FASE E DI SMAN 2 LUBUK SIKAPING - Deli Safitri; Triyono, Joni Adison (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the presence of students who have poor communication skills, lack responsibility, and show a lack of mutual support within their families. Additionally, some students exhibit deficiencies in cooperation skills, self-control skills, and communication skills. The purpose of this study is to determine: 1) the family harmony of tenth-grade students in phase E at SMAN 2 Lubuk Sikaping, 2) the social skills of tenth-grade students in phase E at SMAN 2 Lubuk Sikaping, and 3) the relationship between family harmony and social skills among tenth- grade students in phase E at SMAN 2 Lubuk Sikaping. This research employs a correlational design, with a population of 248 students and a sample of 124 students selected using proportional random sampling. The instrument used in this study is a questionnaire. Data analysis includes percentage calculations and correlation tests. The results of this study indicate that: 1) the family harmony of students at SMAN 2 Lubuk Sikaping falls into the low category; 2) the social skills of phase E students at SMAN 2 Lubuk Sikaping are also in the low category; and 3) there is a relationship between family harmony and social skills among phase E students at SMAN 2 Lubuk Sikaping, with a fairly weak correlation coefficient and a significance value of 0.000. Based on these findings, it is recommended that parents create a harmonious family atmosphere to support the development of their children’s social skills. Furthermore, school counselors are expected to design counseling programs aimed at improving students’ social skills.